TWO COMPETING PALEOMAGNETIC DIRECTIONS IN THE LATE VENDIAN: NEW DATA FOR THE SW REGION OF THE SIBERIAN PLATFORM - Shatsillo A.V.; Didenko A.N.; Pavlov V.E. (My University, 2005)
New paleomagnetic data have been obtained for the Late Vendian sedimentary rocks of the East Sayan and Southwest Baikal regions in the southwest of the Siberian platform. Two substantially different paleomagnetic components are isolated within the investigated stratigraphic interval in all objects of study. The prefolding age of these components, as well as their difference from all of the known Phanerozoic paleomagnetic directions of the Siberian platform, indicate the almost simultaneous formation of the respective magnetization components during the earliest stages of the existence of these rocks. The angular distance between the paleomagnetic poles calculated for these components is about 45°. The analysis of the World Paleomagnetic Database shows that the presence of the discordant paleomagnetic directions in the Vendian-Early Cambrian rocks is characteristic not only of the Siberian objects but is also manifested in other continents and, hence, can be considered as the phenomenon of the planetary scale. We reckon that this fact can be explained by the anomalous behavior of the magnetic field of the Earth around the Precambrian-Cambrian boundary. In this paper we suggest a model describing the "geometry'' of the Earth magnetic field in the Late Vendian-Early Cambrian, which allows one to explain the observed pattern of the paleomagnetic record.
Keywords: PALEOMAGNETISM; VENDIAN; CAMBRIAN; SIBERIAN PLATFORM; ANOMALOUS GEOMAGNETIC FIELD BEHAVIOR; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский; Палеозой::Кембрийская; Paleozoic::Cambrian